An Anthropological study on the socio-economic condition of the small-scale poultry farmers in Bangladesh - Islam, Adhiti Fatema (Brac University, 2023)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Social Sciences in Economics, 2022.